2021
DOI: 10.21037/apm-20-1453
|View full text |Cite
|
Sign up to set email alerts
|

A 4-week, randomized, double-masked study to evaluate efficacy of deproteinized calf blood extract eye drops versus sodium hyaluronate 0.3% eye drops in dry eye patients with ocular pain

Abstract: Background: To evaluate the clinical efficiency of the treatment of dry eye disease (DED) with ocular pain using deproteinized calf blood extract (DCBE) eye drops as compared to 0.3% sodium hyaluronate (SH) eye drops.Methods: This prospective, single-center, masked (double-blind), randomized controlled study included 53 patients divided into two groups: DCBE (n=22) and SH (n=31) group. The DCBE group received DCBE eye drops for 4 weeks, and the SH group received 0.3% SH eye drops for 4 weeks. Corneal fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
(27 reference statements)
0
10
0
Order By: Relevance
“… 2018 ; Wu et al. 2021 ). Studies where the effects of HA treatment could not be isolated for other reasons were excluded (Laflamme & Swieca 1988 ; Ibrahim et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 2018 ; Wu et al. 2021 ). Studies where the effects of HA treatment could not be isolated for other reasons were excluded (Laflamme & Swieca 1988 ; Ibrahim et al.…”
Section: Resultsmentioning
confidence: 99%
“…The same search term in PubMed on the 20th of September 2021 produced 351 results. Studies that investigated eye drops containing HA along with other active ingredients like steroids, cyclosporine, trehalose, or polyethylene glycol were excluded if the effect of HA could not be isolated (Versura et al 2010;Montani 2013;Macri et al 2015;Pinto-Bonilla et al 2015;Kim et al 2017;Rolando & Vagge 2017;Fariselli et al 2018;Fondi et al 2018;Wu et al 2021). Studies where the effects of HA treatment could not be isolated for other reasons were excluded (Laflamme & Swieca 1988;Ibrahim et al 2012;Kamiya et al 2012;C ß akır et al 2018).…”
Section: Review Of Existing Literaturementioning
confidence: 99%
“…Blood-derived tear preparations contain various growth factors, vitamins, and cytokines and could be considered more similar to natural tears than commercially available over-the-counter artificial tear products. Such tear preparations can be derived from a patient's own serum as autologous serum tears, from platelet rich plasma, or from allogeneic sources, such as donor cord blood (Tsubota et al, 1999a;Wu et al, 2021). Serum has been shown to promote the differentiation of corneal and conjunctival epithelial cells to express mucins (Gipson et al, 2003).…”
Section: Blood-derived Tear Preparationsmentioning
confidence: 99%
“…They are applicable to moderate to severe dry eye with ocular surface damage and corneal pain. In a clinical study, calf serum deproteinized extract was shown to be more effective than 0.3% sodium hyaluronate drops in relieving eye pain and photosensitivity in patients with dry eye [158].…”
Section: Ophthalmic Serum Preparationsmentioning
confidence: 99%